2009
DOI: 10.1097/cad.0b013e3283144610
|View full text |Cite
|
Sign up to set email alerts
|

The metal-binding domain of IGFBP-3 selectively delivers therapeutic molecules into cancer cells

Abstract: Conventional chemotherapy for cancer has limited specificity for cancer cells. Here, we investigate the possibility of improving the selectivity of chemotherapy by coadministering targeted biological modifier peptides. We show that the 22-amino acid metal-binding transporter domain (MBD) derived from insulin-like growth factor-binding protein-3 selectively targets cancer cells. The rate of MBD uptake by cells was measured using a panel of 54 human cancer cell lines and correlated with MBD cross-linking to cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…In our study, IGFBP-3 C-terminal peptides readily entered cells as CPPs in a GAG-dependent manner, extending previously published studies demonstrating their cell penetrating property [16,18,28]. GAGs exist in animals as a part of heavily glycosylated proteoglycans, the other component being the core proteins.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In our study, IGFBP-3 C-terminal peptides readily entered cells as CPPs in a GAG-dependent manner, extending previously published studies demonstrating their cell penetrating property [16,18,28]. GAGs exist in animals as a part of heavily glycosylated proteoglycans, the other component being the core proteins.…”
Section: Discussionsupporting
confidence: 86%
“…However, the upstream 8-mer sequence (KK-8) that contains 5 basic lysine residues was not able to permeate into the cells at all. Previously it was suggested that the 12-mer Cys-Cys loop in the peptide QW-14 may be important for its uptake activity [18], but in our study the replacement of the first cysteine in position 224 of the loop with glycine (QW-14mut) did not weaken the uptake much in both wt CHO K1 and the heparan sulfate-deficient pgs D-677 cells (Fig. 5-IIB and C).…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations